Peculiarities of Implementing a Director’s Idea in Contemporary Audiovisual Art - Ганна Чміль; Максим Вітошкін (Вісник Київського національного університету культури і мистецтв. Серія: Аудіовізуальне мистецтво і виробництво)
The purpose of the research is to analyse the peculiarities of the implementation of the director’s idea in fiction and documentary films using new hybrid genres that influence the specifics of contemporary audiovisual art, to determine the role of the mockumentary genre in modern cinema and to understand its impact on the creation of a film product. To explore the psychological impact of documentary films on the viewer’s perception and change of their worldview. To outline the standard and distinctive features of the director’s approach to making documentaries and fiction films. The research methodology is based on the following scientific methods: theoretical – for analysing the psychological factors that influence the perception of an audiovisual work, understanding outstanding examples of world cinema; comparative – for drawing parallels between fiction and documentary cinema. The research also uses structural-systemic and general scientific theoretical research methods (analysis, synthesis, induction, deduction, generalisation, classification, etc.) The scientific novelty is that, for the first time, the approaches to documentary and fiction filmmaking are compared; the details of the phenomenon of the hybrid cinematic genre of mockumentary are established, and its psychological impact on the viewer is studied; the influence of the mockumentary genre on the formation of an audiovisual work through associative editing is outlined. Conclusions. The article analyses the embodiment of the director’s idea in fiction and documentary cinema with the help of new hybrid genres that influence the specifics of contemporary audiovisual art. The role of the mockumentary genre in modern cinema is determined, and its influence on the creation of a film product is studied. The psychological factors of the viewer’s perception of documentary cinema, which help to change their worldview, are investigated.